2008
DOI: 10.1093/jpe/rtn017
|View full text |Cite
|
Sign up to set email alerts
|

Support for the predictions of the pollinator-mediated stabilizing selection hypothesis

Abstract: Floral traits are frequently used in tradition al plant systematics beca use of their assumed constancy. One potential reason for th e apparent constancy of flower size is that effective pollen transfer between flowers depends on the accuracy of the physical fit between the flower and pollinator. Therefore, flowers are likely to be under stronger stabili zing selection for uniform size than vegetative plant parts. Moreover, as pred icted by the pollinator-mediated stabil izing selection (PMSS) hypothes is, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
4
17
0
Order By: Relevance
“…Zygomorphic flowers were visited more frequently by large and medium bees than actinomorphic flowers as previously reported (Goldblatt and Manning, 2006; Gong and Huang, 2009; Knapp, 2010; Sakai et al, 2013), but the functional‐group diversity of pollinators did not differ between symmetry types. Zygomorphic flowers had significantly lower flower‐size variation than actinomorphic flowers did, similar to previous studies (Wolfe and Krstolic, 1999; Ushimaru et al, 2007a; Herrera et al, 2008; van Kleunen et al, 2008; Gong and Huang, 2009), but unlike in previous studies, the flower‐size variation did not vary with functional‐group diversity of the pollinators (Gong and Huang, 2009). Instead, flower‐size variation was related to pollinator composition (the relative frequency of large and medium bee visits), although this significant (only in the GLM) effect disappeared when we examined the direct effect of zygomorphy as the covariate.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Zygomorphic flowers were visited more frequently by large and medium bees than actinomorphic flowers as previously reported (Goldblatt and Manning, 2006; Gong and Huang, 2009; Knapp, 2010; Sakai et al, 2013), but the functional‐group diversity of pollinators did not differ between symmetry types. Zygomorphic flowers had significantly lower flower‐size variation than actinomorphic flowers did, similar to previous studies (Wolfe and Krstolic, 1999; Ushimaru et al, 2007a; Herrera et al, 2008; van Kleunen et al, 2008; Gong and Huang, 2009), but unlike in previous studies, the flower‐size variation did not vary with functional‐group diversity of the pollinators (Gong and Huang, 2009). Instead, flower‐size variation was related to pollinator composition (the relative frequency of large and medium bee visits), although this significant (only in the GLM) effect disappeared when we examined the direct effect of zygomorphy as the covariate.…”
Section: Discussionsupporting
confidence: 83%
“…Zygomorphic species generally exhibit lower flower‐size variation than actinomorphic species in communities worldwide (Wolfe and Krstolic, 1999; Ushimaru et al, 2007a; Herrera et al, 2008; van Kleunen et al, 2008; Gong and Huang, 2009), although some exceptions have been reported recently (Lázaro and Totland, 2014). This trend has been attributed to the fact that specialized pollinator systems, which depend on a limited functional group of pollinators with similar body size and foraging behavior, have provided stronger stabilizing selection on flower size in zygomorphic species than in actinomorphic species with generalized pollinator systems (Table 1; the low pollinator diversity hypothesis, which is usually referred to as the pollinator‐mediated stabilizing selection hypothesis) (Berg, 1960; Armbruster et al, 1999; Wolfe and Krstolic, 1999; Ushimaru et al, 2007a; van Kleunen et al, 2008; Gong and Huang, 2009; Lázaro and Totland, 2014; Rosas‐Guerrero et al, 2014). In support of this hypothesis, Gong and Huang (2009) demonstrated that the lower size variation in zygomorphic flowers was explained well by the positive correlation between flower‐size variation and functional‐group diversity of the pollinators.…”
Section: Summary Of Differences In the Predictions Among The Three Hymentioning
confidence: 99%
“…Several comparisons of variation in floral traits have demonstrated that bilateral flowers were less variable in size than radial flowers (Armbruster et al 1999;Wolfe & Krstolic 1999;Ushimaru et al 2007;Herrera et al 2008;van Kleunen et al 2008), supporting the PMSS hypothesis. However, it remains unclear whether variance in the flower size is associated with pollinator diversity.…”
Section: Introductionmentioning
confidence: 74%
“…Traits that have been subject to consistent stabilizing selection are expected to show limited variation (Cresswell, 1998;Fenster, 1991;Van Kleunen, Meier, Saxenhofer, & Fischer, 2008), and in this situation experimental crosses between divergent populations (Schemske & Bradshaw, 2008;Toräng et al, 2017) or phenotypic manipulation (Campbell, 2009;Peakall & Handel, 1993) may be required to characterize the relationship between trait expression and components of fitness. For example, effects of plant height on pollinator visitation in the sexually deceptive orchid Chiloglottis trilabra were documented only when the range of plant height was extended well beyond the natural variation (Peakall & Handel, 1993).…”
Section: Discussionmentioning
confidence: 99%